Prescription for progress: business process innovation - Marshall, Philip A.F. (Ernst & Young DallasUS, 1993)
Discusses business process innovation and why it may be appropriate to our emerging competitive imperatives in the Caribbean region and reviews the steps and critical success factors necessary to achieve the kind of dramatic changes possible through this approach.